Associations between choroidal thickness and rate of axial elongation in orthokeratology lens users - Riping Zhang; Suoqing Zhuang; Youming Zhou; Man Pan Chin; Lixia Sun; Vishal Jhanji; Mingzhi Zhang (Photodiagnosis and Photodynamic Therapy, 2025)
Objective: To investigate the impact of using orthokeratology lenses (OK lenses) for one year on the axial length (AL) and choroidal thickness (ChT) in the 6 mm concentric central retinal region. Methods: 36 myopic children (36 eyes) aged 8 to 16 years were enrolled. For the duration of one year, the OK group (18 subjects) utilized OK lenses, while the spectacles group (18 subjects) utilized single-vision spectacles as a control. Only their right eyes were used for analysis. ChT in nine regions of the retina was evaluated using optical coherence tomography. AL and other ocular parameters were measured using optical biometry. The measurements were obtained at baseline, 3 months, 6 months, and 12 months. Results: After 12 months of treatment, the OK group showed a reduced rate of AL elongation. The first interval (baseline to 3 months) saw the most notable alteration (p < 0.0001). ChT increased in most regions after wearing OK lenses, except for the nasal retinal region. However, the alteration in nasal ChT exhibited the strongest association with the alteration in AL. Conclusion: The efficacy of myopia control with OK lenses is most pronounced during the initial months of wear. Alterations in the thickness of the nasal choroidal region may correlate with the elongation of the AL, implying its potential role as a biomarker for assessing the efficacy of OK lenses in myopia control.